Why Do Politicians Intervene in Accounting Regulation? The Role of Ideology and Special Interests - JANNIS BISCHOF; HOLGER DASKE; CHRISTOPH J. SEXTROH (Journal of Accounting Research, 2020)
Politicians frequently intervene in the regulation of financial accounting. Evidence from the accounting literature shows that regulatory capture by special interests helps explain these interventions. However, many accounting rules have broad economic or social consequences, such as their effects on income distribution or private sector subsidies. The perception of these consequences varies with a politician's ideology. Therefore, if accounting rules produce those consequences, ideology plausibly spills over and explains a politician's stance on the technical accounting issue, beyond special interest pressure. We use two prominent U.S. political debates about fair value accounting and the expensing of employee stock options to disentangle the role of ideology from special interest pressure. In both debates, ideology explains politicians' involvement at exactly those points when the debate focuses on the economic consequences of accounting regulation (i.e., bank bailouts and top management compensation). Once the debates focus on more technical issues, connections to special interests remain the dominant force.
Keywords: 650; G01; G28; K22; L51; M40; M41; M48; P16; accounting regulation; fair value; financial crisis; ideology; political economy; accounting standard setting; stock option expensing